2012
DOI: 10.1186/1472-6793-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Localization of lipoprotein lipase and GPIHBP1 in mouse pancreas: effects of diet and leptin deficiency

Abstract: BackgroundLipoprotein lipase (LPL) hydrolyzes triglycerides in plasma lipoproteins and enables uptake of lipolysis products for energy production or storage in tissues. Our aim was to study the localization of LPL and its endothelial anchoring protein glycosylphosphatidylinositol-anchored high density lipoprotein-binding protein 1 (GPIHBP1) in mouse pancreas, and effects of diet and leptin deficiency on their expression patterns. For this, immunofluorescence microscopy was used on pancreatic tissue from C57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…It is assumed, but seldom demonstrated, that heparin removes essentially all LPL from the capillary endothelium in tissues (1,38). Determination of LPL activity in post-heparin plasma has been used for many years as a surrogate measure of the functional pool of LPL on the capillary bed in the body.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed, but seldom demonstrated, that heparin removes essentially all LPL from the capillary endothelium in tissues (1,38). Determination of LPL activity in post-heparin plasma has been used for many years as a surrogate measure of the functional pool of LPL on the capillary bed in the body.…”
Section: Discussionmentioning
confidence: 99%
“…The following primary antibodies were used: anti-MBP (1:100; Abcam, ab7349), -dMBP (1:2000; Millipore, ab5864) [31], -βAPP (1:100; Invitrogen, 51-2700), -SMI-31 (1:1000; Covance, smi-31R), -Iba1 (1:600; Wako, 019-19741), -BrdU (1:250; Abcam, ab1893), -GFAP (1:200; Invitrogen, 13-0300), -iNOS (1:100; BD Pharmingen, 610329), -LPL (1:400, from Dr. G. Olivecrona) [57] and -MHC II (1:100; BD Pharmingen, 553549). Images were acquired using a Nikon Eclipse 90 i fluorescent and bright field microscope and analyzed for quantitation with the Metamorph 7.7 software.…”
Section: Methodsmentioning
confidence: 99%
“…At the level of lipid entry into beta cells, one histological analysis has found that lipoprotein lipase (LPL), important for cleaving triglyceride to allow fatty acid entry into cells, is surprisingly not intravascular in mouse islets, but instead appears to be intracellular, where it would not have access to circulating triglyceride [41]. Islet expression of LPL was not altered by fasting-fed state, but was regulated by leptin [41].…”
Section: Intracellular Mechanisms Of Lipotoxicitymentioning
confidence: 99%
“…Islet expression of LPL was not altered by fasting-fed state, but was regulated by leptin [41]. Islet lipid uptake may be regulated by signals that change LPL location to extracellular; disruption of these signals may contribute to reduction of the lipid component of glucose stimulated insulin secretion (GSIS).…”
Section: Intracellular Mechanisms Of Lipotoxicitymentioning
confidence: 99%